Aplikasi Michat Sebagai Media Prostitusi Online Dan Dampaknya Terhadap Pendidikan - Azahra, ‎ Fatma; Aprison, Wedra (ANTHOR: Education and Learning Journal, 2022)
This study aims to find an overview of online prostitution activity patterns through the ‎MiChat application. Finding competition in online prostitution through the MiChat application and the influence of online prostitution on education. The research method used in this study is qualitative. The selected data source is purposive sampling. The criteria for informants in this study are commercial sex workers who work online, aged 20-35 years. Data collection was carried out using observation techniques and interviews with 3 (three) informants namely Mirna, Ayu, and Nina, and documentation. ‎Furthermore, data analysis was carried out through data reduction, data presentation, and concluding. The results of the study show that: (1) Patterns of online prostitution activity through the MiChat application are divided into two, namely working with pimps and independently. Commercial sex workers who work with their pimps only have to serve guests. Meanwhile, commercial sex workers who work independently must carry out their promotions and negotiations. (2) The competition that occurs in online prostitution, namely with colleagues who have the same profession, with fraudsters who take advantage and appearances so that they can maintain the existence of Commercial Sex Workers. Based on the results of this study, it is recommended to block sites The internet, which provides all things related to prostitution and pornography, needs to be improved, the control of the government and law enforcement officials on internet sites and their use, even though there are laws against prostitution, but an effective way to deal with them is for everyone to fortify themselves. yourself and your family by strengthening morals with religious values ​​and other values.